Groundwater recharge and capillary rise in a clayey catchment: modulation by topography and the Arctic Oscillation - T. M. Schrøder; D. Rosbjerg (Copernicus Publications, 2004)
The signature left by capillary rise in the water balance is investigated for a 16 km 2 clayey till catchment in Denmark. Integrated modelling for 1981–99 substantiates a 30% uphill increase in average net recharge, caused by the reduction in capillary rise when the water table declines. Calibration of the groundwater module is constrained by stream flow separation and water table wells. Net recharge and a priori parameterisation has been estimated from those same data, an automatic rain gauge and electrical sounding. Evaluation of snow storage and compensation for a simplified formulation of unsaturated hydraulic conductivity contribute to a modelling of the precipitation-runoff relation that compares well with measurements in other underdrained clayey catchments. The capillary rise is assumed to be responsible for a 30% correlation between annual evapotranspiration and the North Atlantic Oscillation. The observed correlation, and the hypothesis of a hemispherical Arctic Oscillation linking atmospheric pressure with surface temperature, suggests that modelled evapotranspiration from clayey areas is better than precipitation records for identifying the region influenced by oscillation. Keywords: catchment modelling, MIKE SHE, capillary rise, degree-day model, climate